Within and around us: the role of republic borders in archaeological theory and practice in former Yugoslavia - Šošić Klindžić, Rajna (2010)
The Socialist Federal Republic of Yugoslavia consisted of six republics and two autonomous provinces. Although it existed for 45 years, Yugoslavian (Federal) archaeology never materialized. This fact at first glance seems positive, but in reality several archaeologies existed within the republics (national) borders, and their presence is clearly visible in research agendas. Cooperation among the republics was present, but not nearly adequate. It was not equally intense in all archaeological periods, but its reflections were present in interpretations of the material culture and social processes in almost every archaeological period. The Communist's regime policy to create Yugoslavian unity never actually affected archaeology. Regional, national archaeologies greatly impacted interpretations of past cultural processes. Self-perception of the republics in regards to “East” and “Balkans”, and especially the growing pursuit by Croatia and Slovenia (western republics) to be recognized as part of “Mitteleuropa” and not the Balkans also reflected on archaeology. This paper explains how the perception of the Balkans and its borders influenced to some extent interpretations and understanding of the transition from hunting and gathering to the sedentary way of life of the region in general.
Projekt MZOS
ENG